Design of a Smart Donation Box Based on IoT - Setiawan, Deni; Hariono, Tholib (NEWTON: Networking and Information Technology, 2023)
This research, entitled "IoT-based Intelligent Charity Box Design", aims to develop a charity box system that utilizes the Internet of Things (Iot) technology to enhance public participation in charity. In this context, the charity box not only serves as a container for storing donations, but is also equipped with features that can automatically monitor and calculate the amount of money inserted. The system uses the Wemos D1 Mini as a microcontroller connected to the Internet, allowing users to access data in real time through a website. In addition, this smart charity box is equipped with a PIR sensor that detects motion and triggers sound on the DFPlayer, as well as a TCS3200 color sensor that counts the paper money entered. Thus, the research not only offers technological solutions, but also seeks to remind the public of the importance of charity in a more interactive and efficient way. The results of this research are expected to benefit the management of charity funds and raise social awareness in the community.